Supporting nonlinear careers to diversify science. - Anna L Vlasits; Monique L Smith; Maria Maldonado; Simone Brixius-Anderko (PLoS Biology, 2023)
Nonlinear careers through academia are increasingly common, but funding agencies and search committees penalize these paths. Why do scientists stray from the beaten path, how do they contribute to science, and how do we level the playing field?